Riluzole But Not Melatonin Ameliorates Acute Motor Neuron Degeneration and Moderately Inhibits SOD1-Mediated Excitotoxicity Induced Disrupted Mitochondrial Ca2+ Signaling in Amyotrophic Lateral Sclerosis - Jaiswal, Manoj Kumar (Frontiers in Cellular Neuroscience, 2017)
Selective motoneurons (MNs) degeneration in the brain stem, hypoglossal motoneurons (HMNs), and the spinal cord resulting in patients paralysis and eventual death is one of the prominent feature of Amyotrophic lateral sclerosis (ALS). Previous studies have suggested the mitochondrial respiratory impairment, importance of low Ca2+ buffering and homeostasis, excitotoxicity and impaired mitochondria in MN degeneration are the pathological phenotypes found in mice and cell culture models of fALS linked with Cu/Zn-superoxide dismutase 1 (SOD1) mutation. In our study, we aim to understand impact of riluzole and melatonin on excitotoxicity, neuronal protection and Ca2+ signalling in individual HMNs in symptomatic adult ALS mouse and in SH-SY5Y WT and G93A-SOD1 transfected neuroblastoma cell line using fluorescence microscopy, calcium imaging with high speed charged cool device (CCD) camera, together with immunohistochmistry, cell survival assay and histology. In our experiments, riluzole but not melatonin ameliorate motor neuron degeneration and moderately inhibit excitotoxicity in SH-SY5YWT or SH-SY5YG93A cell lines induced by sodium azide. Riluzole significantly inhibit cell death induced by inhibiting the mitochondrial electron transport chain by Na-azide. In the HMNs of brainstem in adult (14-15 weeks) WT, and corresponding symptomatic SOD1G93A mice, we measured the effect of riluzole and melatonin on [Ca2+]i using fura-2 AM ratiometric calcium imaging in individual MNs. Riluzole caused a significant decrease in [Ca2+]i transients and reversibly inhibited [Ca2+]i transients in fura-2 AM loaded hypoglossal motoneurons exposed to Na-azide in adult symptomatic SOD1G93A mice. On the contrary, melatonin failed to show similar effects in the HMNs of WT and SOD1G93A mice. Intrinsic NADH fluorescence, an indicator of mitochondrial metabolism and health in MNs showed enhanced intrinsic NADH fluorescence in HMNs in presence of riluzole when respiratory chain activity was inhibited by Na-azide. Riluzole’s inhibition of excitability and Ca2+ signaling may be due to its multiple effects on cellular function of mitochondria and therefore formulating a drug therapy to stabilise mitochondria-related signaling pathways might be a valuable approach for cell death protection in ALS. Taken together, the pharmacological profiles of the riluzole and melatonin strengthen the case that riluzole indeed can be used as a therapeutic agent in ALS whereas claim